DISTRIBUSI SALINITAS ESTUARIA DELTA MAHAKAM PERAIRAN KUTAI KARTANEGARA - Riyadi, Agung (Jurnal Hidrosfir Indonesia, 2006)
Many estuary have a different salinity distribution, influence for the differentlevel of tide, river discharge flow, velocity and current direction. Januari 2006 at Delta Mahakam, going to salinity measurement activity covered by four village closed to the sea, that is Kersik, Marang Kayu, Muara Jawa and Muara Kembang. Water deep at Delta Mahakam relatif shallow, around 0.5 9 meter. Every estuary founded 2 5 point measurement salinity from the surface water until bottom and found the different for the salinity distribution. Kersik region have a higher salinity until 30 psu, whereas at the Muara Kembang region salinity level only 12 psu with a distance from the coast line about 3 km. This location similar with the Muara Jawa region. Pattern circulation and stratification water estuary base for clasification, Marang Kayu region have a mix completelly or vertical homogeneous estuary, while a Kersik, Muara Kembang and Muara Jawa region have a moderat sratification estuary. This type is very common in Indonesia, fresh water flow throungh to the river very dominant at several estuary.